Combined laparoscopic ovariectomy and laparoscopic‐assisted gastropexy versus combined laparoscopic ovariectomy and total laparoscopic gastropexy: A comparison of surgical time, complications and postoperative pain in dogs. Issue 3 (3rd February 2020) - Leonardi, Fabio; Properzi, Roberto; Rosa, Jessica; Boschi, Paolo; Paviolo, Silvia; Costa, Giovanna L.; Bendinelli, Cristiano
Abstract: The trend in laparoscopy is to develop easy and rapid techniques associated with reduced intraoperative complications and decreased postoperative pain. The aim of this study was to compare combined laparoscopic ovariectomy (OIE) and laparoscopic‐assisted incisional gastropexy (LAG) with combined laparoscopic OIE and total laparoscopic gastropexy (TLG) for surgical time, incidence of complications and postoperative pain. Twenty‐eight female dogs were randomly assigned to the LAG group ( n  = 14) or the TLG group ( n  = 14). All laparoscopic procedures were performed using a three‐port technique. The gastropexy was located 3 cm caudal to the 13th rib and 4 cm lateral to the rectus abdominis muscle. Surgical time (minutes [min]), intraoperative complications and postoperative complications were recorded. The Glasgow pain score (GPS) (short form) was calculated before surgery and at 1, 6, 12, 18 and 24 hr after extubation. Surgical time was significantly longer in the TLG group (48 ± 2 min) compared with the LAG group (39 ± 2 min). Minor postoperative complications occurred in both groups and included swelling ( n  = 2) and subcutaneous emphysema ( n  = 1). No significant differences regarding the GPS were recorded between groups. The GPS was significantly higher in both groups at 1 hr and 6 hr than before surgery. Two dogs in each group required rescue analgesia. Combined laparoscopic OIE and TLG require more time to perform than combined laparoscopic OIE and LAG. Neither procedure results in significant surgical complications. Postoperative pain for 24 hr was mild and comparable in both groups. Abstract : Combined laparoscopic ovariectomy (OIE) and total laparoscopic gastropexy (TLG) requires more time to perform than combined laparoscopic OIE and laparo‐assisted gastropexy (LAG). Neither procedure results in significant surgical complications. Postoperative pain for 24 hr was mild and comparable in dogs undergoing combined OIE and TLG or combined OIE and LAG.